An ultrawideband Vivaldi antenna with enhanced feeding system - Golovkov, A.A.; Kalinikos, D.A.; Kiselev, B.A.; Golubeva, E.Yu; Sugak, M.I.; Khaikin, V.B. (CriMiCo 2002 : 12th International Conference "Microwave & Telecommunication Technology" : conference proceedings, September 9-13, 2002, Sevastopol, Crimea, Ukraine, 2002)
Simulated and measured results of an ultrawideband Vivaldi radiators are presented. An enhanced feeding system of this antenna allows us to increase the operating frequency band. A good matching (VSWR better than 2) in the prototype and sufficiently low insertion losses over a three-octave frequency interval were reached.